2014
DOI: 10.1158/0008-5472.can-13-3383
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Retrograde Signaling Mediated by UCP2 Inhibits Cancer Cell Proliferation and Tumorigenesis

Abstract: Cancer cells tilt their energy production away from oxidative phosphorylation (OXPHOS) toward glycolysis during malignant progression, even when aerobic metabolism is available. Reversing this phenomenon, known as the Warburg effect, may offer a generalized anticancer strategy. In this study, we show that overexpression of the mitochondrial membrane transport protein UCP2 in cancer cells is sufficient to restore a balance toward oxidative phosphorylation and to repress malignant phenotypes. Altered expression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 50 publications
2
73
0
Order By: Relevance
“…Despite the apparent discrepancies concerning the role of UCP2 in carcinogenesis and cancer progression in different types of cells, e.g. UCP2 inhibition of apoptosis in hypoxia, our findings are in accordance with recent reports that UCP2 represses the malignant phenotypes of melanoma, glioma, and pancreatic cancer cells and that UCP2 deficiency mimics the effects of hypoxia in pulmonary hypertension [10, 11, 24, 25]. UCP2 was also shown to downregulate HIF-1, which, together with our finding that HIF-1 mediated hypoxia-triggered silencing of UCP2, suggests a regulatory circuit between UCP2 and HIF-1 determining the phenotypes of hypoxic malignant cells [10].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Despite the apparent discrepancies concerning the role of UCP2 in carcinogenesis and cancer progression in different types of cells, e.g. UCP2 inhibition of apoptosis in hypoxia, our findings are in accordance with recent reports that UCP2 represses the malignant phenotypes of melanoma, glioma, and pancreatic cancer cells and that UCP2 deficiency mimics the effects of hypoxia in pulmonary hypertension [10, 11, 24, 25]. UCP2 was also shown to downregulate HIF-1, which, together with our finding that HIF-1 mediated hypoxia-triggered silencing of UCP2, suggests a regulatory circuit between UCP2 and HIF-1 determining the phenotypes of hypoxic malignant cells [10].…”
Section: Discussionsupporting
confidence: 91%
“…UCP2 plays a role in the regulation of cell survival by affecting ROS generation, redox status, and ATP production [9, 11]; therefore, we examined whether UCP2 is involved in the hypoxia-mediated desensitization of NSCLC cells to chemotherapy. Our results showed that UCP2 expression was downregulated in malignant tissues of patients with COPD and NSCLC compared with that in patients with NSCLC alone, suggesting a role of COPD-related hypoxia in regulating UCP2 expression (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HK2 is a predominant isoform in proliferating cells and its upregulation has been known to be a major contributor to the elevated glycolysis observed in many types of tumor cells [14]. In contrast, UCP2 expression level correlates negatively with proliferation of cancer cells [21], which also involves metabolic reprogramming, i.e., decreased glycolysis and increased oxidative phosphorylation in cancer cells overexpressing UCP2 [21]. This altered metabolism may inhibit adipogenic and osteogenic differentiation of G6PT À/À MSCs, since a metabolic switch from glycolysis to oxidative phosphorylation has been known to occur during adipogenic and osteogenic differentiation of MSCs derived from bone marrow and adipose tissues [22,23].…”
Section: Discussionmentioning
confidence: 99%